Maternal and Child Characteristics Associated With Mother–Child Interaction in One‐Year‐Olds. Issue 4 (18th April 2017) - Graff, J. Carolyn; Bush, Andrew J.; Palmer, Frederick B.; Murphy, Laura E.; Whitaker, Toni M.; Tylavsky, Frances A.
Abstract: Mothers' interactions with their young children have predicted later child development, behavior, and health, but evidence has been developed mainly in at‐risk clinical samples. An economically and racially diverse sample of pregnant women who were not experiencing a high‐risk pregnancy were recruited to participate in a community‐based, longitudinal study of factors associated with child cognitive and social‐emotional development during the first 3 years. The purpose of the present analysis was to identify associations between the characteristics of 1125 mothers and their 1‐year‐olds and the mothers' and children's scores on the Nursing Child Assessment Teaching Scale (NCATS). A multivariable approach was used to identify maternal and child characteristics associated with NCATS scores and to develop prediction models for NCATS total and subscale scores of mothers and children. Child expressive and receptive communication and maternal IQ, marital status, age, and insurance predicted NCATS Mother total score, accounting for 28% of the score variance. Child expressive communication and birth weight predicted the NCATS Child total score, accounting for 4% of variance. Child's expressive communication and mother's IQ and marital status predicted NCATS mother‐child total scores. While these findings were similar to reports of NCATS scores in at‐risk populations, no previous teams examined all of the mother and child characteristics included in this analysis. These findings support the utility of the NCATS for assessing mother‐child interaction and predicting child outcomes in community‐based, non‐clinical populations. © 2017 Wiley Periodicals, Inc.